2011
DOI: 10.1111/j.1530-0277.2011.01628.x
|View full text |Cite
|
Sign up to set email alerts
|

Prazosin Effects on Stress‐ and Cue‐Induced Craving and Stress Response in Alcohol‐Dependent Individuals: Preliminary Findings

Abstract: Background Stress, alcohol cues and dysregulated stress responses increase alcohol craving and relapse susceptibility, but few pharmacologic agents are known to decrease stress and cue-induced alcohol craving and associated stress dysregulation in humans. Here we report findings from a preliminary efficacy study of the alpha1 receptor antagonist, prazosin, in modulating these relapse-relevant factors in alcohol dependent (AD) individuals. Methods Seventeen early abstinent, treatment-seeking alcohol dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 71 publications
2
117
2
1
Order By: Relevance
“…Our study obtained craving-and distress-responses of a magnitude very similar to that reported in non-selected alcohol-dependent patients (see eg, Sinha et al, 2011), and shown to be sensitive to pharmacological effects (Fox et al, 2012). We did not directly evaluate the clinical efficacy of pexacerfont in alcoholism, and limited data are available to determine the predictive validity of the surrogate markers we obtained.…”
Section: Discussionmentioning
confidence: 59%
“…Our study obtained craving-and distress-responses of a magnitude very similar to that reported in non-selected alcohol-dependent patients (see eg, Sinha et al, 2011), and shown to be sensitive to pharmacological effects (Fox et al, 2012). We did not directly evaluate the clinical efficacy of pexacerfont in alcoholism, and limited data are available to determine the predictive validity of the surrogate markers we obtained.…”
Section: Discussionmentioning
confidence: 59%
“…Prazosin treatment also facilitates abstinence in treatment-seeking alcohol-dependent men, as demonstrated in a study in which the subjects were unaware of their treatment condition (prazosin vs placebo) and there were no differences in side effects reported (Simpson et al, 2009). In addition, prazosin decreases stress-and cue-induced alcohol craving in alcohol-dependent men and women (Fox et al, 2012). The present study investigated whether prazosin, administered only at the time of stress during alcohol deprivation, would block increases in anxiety behavior after alcohol reinstatement and an additional deprivation.…”
Section: Introductionmentioning
confidence: 83%
“…Also, drugs such as Prazosin, an alpha-1 adrenergic antagonist, might be considered as adjunct pharmacotherapy for individuals who are particularly troubled by DD. This drug is considered an effective treatment for posttraumatic stress disorder nightmares (Kung et al, 2012), and there is preliminary evidence that it can reduce craving precipitated by stress and exposure to drug cues (Fox et al, 2012). Incidentally, if DDs are partly reflective of craving and negative affect experienced during the day as a result of withdrawal, then clinical approaches to reduce their impact could be conceived as a broader withdrawal management strategy.…”
Section: Discussionmentioning
confidence: 99%